Penggunaan Bahan Pengisi terhadap Mutu Nugget Vegetarian Berbahan Dasar Tahu dan Tempe - Syarifah Rohaya; Nida El Husna; Khairul Bariah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2013)
The purpose of this study was to compare different sources of flours and protein sources based on soya bean products in producing vegetarian nugget. Factorial experimental design with three replications was employed where wheat, sweet potato, sago and banana flour as one factor, and tempeh and tofu as another factor. Moisture and raw protein content of vegetarian nuggets produced in this study was in accordance with the Indonesia Standard (SNI). Moisture was less than 60 percent and raw protein was above 12 percent. The highest organoleptic test was obtained from the nugget made of the combination of sago as filler and tofu as protein source. The nugget contained 60.00, 14.89, 28.89 and 2.00 percent of moisture, raw protein, raw fat and ash content, respectively. The organoleptic scores were 2.70, 3.58, 3.50, 3.53 and 3.62 for color, aroma, taste, texture and springiness, respectively.Keywords: nugget, vegetarian nugget, filler